2021
DOI: 10.3390/nu13103321
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Vitamin D Levels in Maternal Sera and Offspring Specific Learning Disorders

Abstract: Recent evidence has suggested potential harmful effects of vitamin D deficiency during pregnancy on offspring brain development, for example, elevated risks for neuropsychiatric disorders. Findings on general cognition and academic achievement are mixed, and no studies have examined the effect of prenatal 25-hydroxyvitamin D (25(OH)D) levels on diagnosed specific learning disorders, which was the aim of this study. We examined a nested case–control sample from the source cohort of all singleton-born children i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
(57 reference statements)
1
3
0
Order By: Relevance
“…affected the risk of language, learning and coordination disorders in offspring to immigrant mothers. The findings are in line with some previous studies that have not found any associations between maternal serum vitamin D and learning-related outcomes, such as academic achievement, IQ or specific learning disorders [11,16,17].…”
Section: Plos Onesupporting
confidence: 93%
See 1 more Smart Citation
“…affected the risk of language, learning and coordination disorders in offspring to immigrant mothers. The findings are in line with some previous studies that have not found any associations between maternal serum vitamin D and learning-related outcomes, such as academic achievement, IQ or specific learning disorders [11,16,17].…”
Section: Plos Onesupporting
confidence: 93%
“…A meta-analysis indicated possible small adverse effects of prenatal vitamin D deficiency on cognitive and language development [ 10 ]. In our previous study including over 3,000 pregnant women, vitamin D deficiency in early pregnancy was not associated with specific learning disorders in offspring in a Finnish sample [ 11 ]. However, some studies have indicated possible effect moderation by race or ethnic group on the associations between prenatal vitamin D levels and developmental outcomes [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, fifteen mother–child studies (n = 20,778) and eight studies in children (n = 7496) showed no association [ 101 ]. A large Finnish nested case-control study (1607 children with learning difficulties with matched controls) also showed no link between maternal 25(OH)D 3 levels and behaviour [ 102 ].…”
Section: Developmental Vitamin D Deficiency Effect On Brain Function ...mentioning
confidence: 99%
“…However, in this study, pre-pregnancy BMI of pregnant women with VD deficiency was unclear [ 110 ]. It has also been reported that maternal VD deficits are linked to cognitive disorders in offspring, including attention-deficit/hyperactivity disorder [ 111 ], schizophrenia [ 112 ], and learning disorders [ 113 ].…”
Section: The Relationship Of Vd Deficiency During Pregnancy and Obesi...mentioning
confidence: 99%